Mastering SQL Server 2017 : Build Smart and Efficient Database Applications for Your Organization with SQL Server 2017. - Radivojević, Milos (Packt Publishing, Limited, 2019)
This Learning Path is a step-by-step guide that covers everything you need to develop efficient data integration and data transformation solutions for your organization.